2017
DOI: 10.5811/westjem.2016.12.32489
|View full text |Cite
|
Sign up to set email alerts
|

Inferior Vena Cava Measurement with Ultrasound: What Is the Best View and Best Mode?

Abstract: IntroductionIntravascular volume status is an important clinical consideration in the management of the critically ill. Point-of-care ultrasonography (POCUS) has gained popularity as a non-invasive means of intravascular volume assessment via examination of the inferior vena cava (IVC). However, there are limited data comparing different acquisition techniques for IVC measurement by POCUS. The goal of this evaluation was to determine the reliability of three IVC acquisition techniques for volume assessment: su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 27 publications
1
51
0
3
Order By: Relevance
“…Although inter‐rater variability for the CVC CI may be high in healthy dogs, it is possible that CVC measurements at this location will have less inter‐rater variability when measured in hypervolemic or hypovolemic dogs. In humans, the greatest variation of IVC CI occurs in healthy populations, with less variation occurring in patients with values outside established reference intervals . However, IVC CI still is widely used in humans in critical care units to determine intravascular status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although inter‐rater variability for the CVC CI may be high in healthy dogs, it is possible that CVC measurements at this location will have less inter‐rater variability when measured in hypervolemic or hypovolemic dogs. In humans, the greatest variation of IVC CI occurs in healthy populations, with less variation occurring in patients with values outside established reference intervals . However, IVC CI still is widely used in humans in critical care units to determine intravascular status.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the greatest variation of IVC CI occurs in healthy populations, 34 with less variation occurring in patients with values outside established reference intervals. 35 In human medicine, the IVC/Ao often is used to assess intravascular volume because it can be used in patients with various weights and body sizes.…”
Section: Reference Values For Echocardiographic Dimensions Related mentioning
confidence: 99%
“…Another way to estimate an individual's intravascular filling state non‐invasively is the ultrasound derived inferior vena cava collapsibility index (IVCI) (Finnerty et al . ). In intensive care patients, IVCI correlates well with invasively measured central venous pressure and pulmonary artery pressure (Stawicki et al .…”
Section: Cardiorenal Syndromesmentioning
confidence: 97%
“…In contrast, plasma volume (PV) expansion is known to be less pronounced in preeclampsia than in uncomplicated pregnancy (De Haas et al 2017), but increased PV has also been reported in late preeclampsia (Friedberg & Lutz, 1963;Schrier & Briner, 1991) with or without persistence of high cardiac output (Easterling et al 1990;Bosio et al 1999). Another way to estimate an individual's intravascular filling state non-invasively is the ultrasound derived inferior vena cava collapsibility index (IVCI) (Finnerty et al 2017). In intensive care patients, IVCI correlates well with invasively measured central venous pressure and pulmonary artery pressure (Stawicki et al 2016;Ilyas et al 2017).…”
Section: Direct Cardiorenal Interactionsmentioning
confidence: 99%
“…Additionally, Caval sonography can be repeated during fluid resuscitation to follow up improvement of these parameters. With B-mode holds the most promise to deliver reliable measures of IVC diameter 26 . The IVC diameter of more than 2.5 cm and minimal collapse (<10%) correlates with raised right atrial pressure >15mm Hg 27 .…”
Section: Introductionmentioning
confidence: 99%